The Role Of Intraventricular Hemorrhage In Mortality And Early Neurological Outcome Of Premature Infants - Mod, Harsh; Akhani, Sonu; Patel, Nawaz Zuberbhai; Vaza, Janak; Shah, Karan; Dihora, Kinjal (Journal of Neonatal Surgery, 2025)
Background: Intraventricular hemorrhage (IVH) remains a major cause of mortality and long-term neurological impairment in preterm neonates. Understanding the associated risk factors is critical for early diagnosis and improved outcomes. Material and Methods: A prospective observational study was conducted at a tertiary care hospital including 100 preterm neonates. Clinical, demographic, prenatal, and perinatal data were collected and analyzed. Cranial ultrasonography was used for diagnosis, and neurodevelopmental outcomes were assessed at discharge. Statistical analyses were performed using SPSS version 25.0, with significance set at p<0.05. Results: The incidence of IVH among preterm neonates was 20%. Significant neonatal risk factors included lower gestational age, lower birth weight, and lower Apgar scores at 1 and 5 minutes. Prenatal factors such as pregnancy-induced hypertension and premature rupture of membranes (PROM) were also associated with an increased risk of IVH. Neurological complications like seizures, hydrocephalus, and posthemorrhagic ventricular dilatation were common in neonates with IVH. Conclusion: Lower gestational age, low birth weight, compromised Apgar scores, PIH, and PROM significantly increased the risk of IVH in preterm neonates. Early identification and preventive strategies are essential to reduce associated morbidity and mortality.